Experimental investigation and evaluation of hybrid solar/thermal dryer combined with supplementary recovery dryer - Yassen, T.A. (Elsevier Ltd, 2016)
The common practice in the hybrid solar dryers which are backed up with thermal source is to exhaust the flue gas to the ambient. This flue gases are still hot and carry considerable amount of thermal energy as waste. In the present work, the thermal energy of flue gas from a biomass thermal backup unit was utilized in terms of heat recovery criteria. A prototype of hybrid solar-thermal drying system was coupled with recovery dryer to yield a combination of the main dryer and the recovery dryer. The combination was investigated experimentally to evaluate the enhanced performance compared to the system without recovery. The investigations were conducted under two operational modes, hybrid mode (day and night) and thermal mode alone (night). Red chili was utilized as drying material. The results of the thermal mode showed that the overall drying efficiency of the dryer was increased from 9.9 without recovery dryer to 12.9 with the recovery dryer. The overall drying efficiency of the hybrid drying without recovery dryer was 10.3, while it was increased to overall drying efficiency of 13 in the case of using hybrid dryer and recovery. The enhancement of the overall drying efficiency due to the recovery dryer was 25.84 in the hybrid day and night drying, and was 29.7 in the night thermal drying mode. This validated enhancement encourages the use of sub dryer as thermal recovery to optimize the utilization of fuel, and to increase the system capacity. Â© 2016 Elsevier Ltd.